2009
DOI: 10.1021/ja9076292
|View full text |Cite
|
Sign up to set email alerts
|

The i-Motif in the bcl-2 P1 Promoter Forms an Unexpectedly Stable Structure with a Unique 8:5:7 Loop Folding Pattern

Abstract: Transcriptional regulation of the bcl-2 proto-oncogene is highly complex, with the majority of transcription driven by the P1 promoter site and the interaction of multiple regulatory proteins. A guanine-and cytosine-rich (GC-rich) region directly upstream of the P1 site has been shown to be integral to bcl-2 promoter activity, as deletion or mutation of this region significantly increases transcription. This GC-rich element consists of six contiguous runs of guanines and cytosines that have the potential to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 81 publications
(205 reference statements)
6
131
1
Order By: Relevance
“…In support of this thesis, non-B DNA structures are known to inhibit replication fork progress (18,20,64) and activate DNA damage checkpoints (35,79). Under physiological conditions, the Pu-rich strand may form G-quadruplex or triplex structures, whereas C-rich strand structures are less likely to occur in vivo as they are stabilized by hemiprotonated C-C ϩ base pairing at acid pH (62,80). Our results demonstrate that the PKD1 IVS21 Pu-Py tract can inhibit primer extension on purified DNA in vitro and in human chromosomes in a polar manner.…”
Section: Discussionmentioning
confidence: 96%
“…In support of this thesis, non-B DNA structures are known to inhibit replication fork progress (18,20,64) and activate DNA damage checkpoints (35,79). Under physiological conditions, the Pu-rich strand may form G-quadruplex or triplex structures, whereas C-rich strand structures are less likely to occur in vivo as they are stabilized by hemiprotonated C-C ϩ base pairing at acid pH (62,80). Our results demonstrate that the PKD1 IVS21 Pu-Py tract can inhibit primer extension on purified DNA in vitro and in human chromosomes in a polar manner.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is now known that certain i-motifs may be stable in vivo [14,15]. There are two kinds of i-motif structures, 5′E and 3′E, determined by the end of the intercalated base pairs at the outside of the structure (Scheme1b) [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The C-rich ssDNA from S. cerevisiae meiosisspecific DSB adopts i-motif conformation Multiple studies have shown that the formation of i-motif structures by C-rich ODNs result in a characteristic retarded mobility of DNA in polyacrylamide gels, and a specific CD spectroscopic signature with a maximum positive peak between 280 and 288 nm and a negative peak within 260-267 nm (63)(64)(65)90). After having shown that the G-rich ssDNA derived from a meiosis-specific DSB folds into intramolecular GQs, we asked whether the C-rich strand complementary to the G-rich sequence can adopt i-motif conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent studies have revealed that both GQ DNA and i-motifs are formed simultaneously within the same double-stranded tract in a variety of DNA templates (62,63). In support of their biological relevance, various studies have found that the i-motif plays a regulatory role in gene expression (64)(65)(66). Indeed, a number of proteins have been shown to bind cytosinerich strands, possibly i-motif structures.…”
Section: Introductionmentioning
confidence: 98%